Prognosis of acute kidney injury during acute heart failure: the role of diuretics. (25th November 2020) - Lombardi, Y; Boccara, F; Baldet, K; Lang, S; Ederhy, S; Nhan, P; Riller, Q; Chauvet-Droit, M; Jean, M.-L; Adavane-Scheuble, S; Azoyan, L; Cohen, A
Abstract: Background: Acute kidney injury (AKI) frequently occurs after diuretic treatment initiation during acute heart failure (AHF). Treatment-induced hemoconcentration seems associated with improved prognosis. Transient AKI, with or without hemoconcentration, is of unsettled prognosis. Purpose: We aimed to determine the independent prognostic values of transient AKI, persistent AKI and hemoconcentration in the context of hospitalized AHF. Methods: Data were obtained from our institution's Clinical Data Warehouse. Patients that visited our unit at least once were screened. All hospitalizations in our institution were examined (>30 hospitals). Inclusion criteria were: ≥1 hospitalization with ≥1 recorded furosemide administration and ≥1 AHF ICD-10 code. Only the first hospitalization fulfilling these criteria was considered. AKI during 1–13 days following first furosemide administration was defined based on Kidney Disease Improving Global Outcome guidelines. Hemoconcentration was defined as an increase in serum proteins ≥5 g/l during the same period. We performed multivariate logistic regression to determine which characteristics were predictive of AKI. We used Cox regression of 100-days all-cause mortality using several confounders to determine the prognostic values of transient AKI (lasting <14 days), persistent AKI (lasting ≥14 days) and hemoconcentration. To account for immortality bias, AKI and hemoconcentration were treated as time-dependent covariates. Results: We included 579 patients in the study. Median follow-up was 114 days. AKI following furosemide initiation occurred in 234 patients (40.4%). Patients that experienced AKI more frequently suffered from chronic kidney disease (43.6% vs. 33%, p=0.01) or presented with right ventricular dilatation (12% vs. 6.7%, p=0.04). Independent predictors of AKI were arterial hypertension (adjusted OR: 1.86 [1.08–3.22]), elevated serum creatinine at baseline (adjusted OR: 1.07 [1.01–1.14] per 10 μmol/l increase) and initial intravenous furosemide (adjusted OR: 2.42 [1.39–4.29]). Death during follow-up occurred in 35% of patients in the AKI group compared to 21% in the non-AKI group (p<0.001). In Cox regression, persistent AKI was independently associated with increased mortality in a period of 100 days following furosemide initiation (adjusted HR: 2.31 [1.07–4.99]). Transient AKI was not significantly associated with mortality (adjusted HR: 0.64 [0.34–1.19]). Hemoconcentration was independently associated with decreased mortality (adjusted HR: 0.46 [0.27–0.79]). Conclusion: In the context of hospitalized AHF, AKI that developed 1–13 days after furosemide initiation and that lasted ≥14 days was independently associated with decreased 100 days survival. Hemoconcentration, using a clinically relevant definition, was independently associated with improved survival. These findings show that serum creatinine and proteins, routinely used and with limited cost, accurately stratify mortality risk during AHF. Funding Acknowledgement: Type of funding source: None